Let I have a sequence as follows,


where $(a_2-a_1),(a_3-a_2),(a_4-a_3),... $ are in arithmetic progression.

How can I find the Nth element ($a_N$) of the series $a_1,a_2,a_3,a_4,...,a_N,..$

I am new in AP Series. Please help.


closed as off-topic by Tom-Tom, Shailesh, N. F. Taussig, Leucippus, Hans Engler Feb 8 '16 at 4:07

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Tom-Tom, Shailesh, N. F. Taussig, Leucippus, Hans Engler
If this question can be reworded to fit the rules in the help center, please edit the question.

  • 3
    $\begingroup$ It's a quadratic. Let $$a_n = xn^2 + yn + z$$ and choose any three elements of the sequence, solve the system of linear equations. $\endgroup$ – Zubin Mukerjee Feb 7 '16 at 21:17


Set $\forall n\in\mathbb N,\,u_n=a_{n+1}-a_n$. $(u_n)_{n\in\mathbb N}$ is an AP so you know the general formula for $\sum_{k=1}^{N-1}u_k$. But this sum is a telescoping one so $\sum_{k=1}^{N-1}u_k=\sum_{k=1}^{N-1}(a_{k+1}-a_k)=a_N-a_1$.


Because the common differences in the sequence are equal, the relationship between $n$ and $a_{n}$ must be quadratic. For a quadratic, $3$ terms are enough to find the exact relation. We let $a_{1} = x + y + z,$ $a_{2} = 4x + 2y + z,$ and $a_{3} = 9x + 3y + z.$

We see that $3x + y = a_{2} - a_{1}$ and $5x + y = a_{3} - a_{2}.$ This leaves $2x = a_{1} + a_{3},$ so $x = \frac{1}{2}\left(a_{1} + a_{3}\right).$

Knowing $x$ and using the first of the equations found previously, we have $$\frac{3}{2}\left(a_{1} + a_{3}\right) + y = a_{2} - a_{1}$$ $$y = a_{2} - \frac{5}{2}a_{1} - \frac{3}{2}a_{3}.$$

Finally, plugging in $x$ and $y$ into the first of the main equations yields $$a_{1} = \frac{1}{2}\left(a_{1} + a_{3}\right) + a_{2} - \frac{5}{2}a_{1} - \frac{3}{2}a_{3} + z$$ $$z = -a_{1} - a_{2} + a_{3}.$$

The relation, using our findings, is $$\boxed{a_{n} = \frac{1}{2}\left(a_{1} + a_{3}\right)n^{2} + \left(a_{2} - \frac{5}{2}a_{1} - \frac{3}{2}a_{3}\right)n - a_{1} - a_{2} + a_{3}}.$$


Not the answer you're looking for? Browse other questions tagged or ask your own question.